2014
DOI: 10.1590/1516-3180.2013.7180005
|View full text |Cite
|
Sign up to set email alerts
|

No association between 25-hydroxyvitamin D levels and prediabetes in Brazilian patients. A cross-sectional study

Abstract: CONTEXT AND OBJECTIVE: Several studies have evaluated the role of low 25-hydroxyvitamin D (25OHD3) in the pathogenesis of type 2 diabetes (T2DM) and have presented controversial results. The metabolic processes that culminate in T2DM begin under prediabetic conditions. Our aim was to analyze the association between 25OHD3 and glucose metabolism in individuals who were free from but at elevated risk of diabetes. DESIGN AND SETTING: Cross-sectional study at a tertiary hospital. METHODS: Anthropometric and labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
1
10
0
2
Order By: Relevance
“…Already at the early stages of the disease, there were initial metabolic deregulations, evidenced by alterations in glucose tolerance during the GTT and ITT, as well as the glucose and insulin levels, indicative of insulin resistance, in agreement with other studies [18,26,27]. At this stage, although fasting glucose levels are maintained within normal values (normoglycemia), due to compensatory hyperinsulinemia, there is already some degree of glucose intolerance and peripheral insulin resistance, in agreement with other reports [18,28,29,30].…”
Section: Discussionsupporting
confidence: 91%
“…Already at the early stages of the disease, there were initial metabolic deregulations, evidenced by alterations in glucose tolerance during the GTT and ITT, as well as the glucose and insulin levels, indicative of insulin resistance, in agreement with other studies [18,26,27]. At this stage, although fasting glucose levels are maintained within normal values (normoglycemia), due to compensatory hyperinsulinemia, there is already some degree of glucose intolerance and peripheral insulin resistance, in agreement with other reports [18,28,29,30].…”
Section: Discussionsupporting
confidence: 91%
“…The authors found no association between vitamin D deficiency and HbA1c levels 7 . In a smaller crosssectional study of Brazilian patients, Giorelli et al 8 found no association between vitamin D levels and the risk of prediabetes. The present findings are in accordance with those of Modi et al 7 and Giorelli et al 8 There are potential explanations for the discrepancies in the present study results, including the size of the effect.…”
Section: Discussionmentioning
confidence: 91%
“…There is a growing debate over the association between low 25hydroxyvitamin D (vitamin D) levels and the risk of diabetes mellitus/prediabetes development 1,2 . A large number of crosssectional studies [3][4][5] , but not all of them [6][7][8] , have shown an inverse association between vitamin D status and impaired glucose tolerance, insulin resistance or diabetes mellitus 9 . Reported data also suggest an association between low vitamin D levels with poor diabetes mellitus control 10,11 and diabetes mellitus related complications 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of vitamin D blood dosage level in the habitual prenatal care could be an interesting action as rickets prophylaxis in newborns and for preeclampsia. We believe, that though this study was the first step, new aspects should be evaluated and addressed in the near future [27][28][29][30][31][32]. But now our results show that low blood levels of vitamin D in the first trimester are associated with pre-eclampsia, but not with birth weight.…”
Section: Discussionmentioning
confidence: 88%